Pemanfaatan Artificial Intelligence dalam Dunia Industri: Analisis Literatur Menggunakan Metode SLR dan Teknik PRISMA - Syafril, Syafril; Veri, Jhon (Indo-MathEdu Intellectuals Journal, 2025)
Artificial Intelligence (AI) has become a key technology in the digital transformation of industries in the era of the Fourth Industrial Revolution. This research aims to analyze the utilization of AI across various industrial sectors through a Systematic Literature Review (SLR) approach by applying the PRISMA protocol to ensure the accuracy and transparency of the literature selection process. Data is obtained from various leading scientific databases with strict inclusion criteria, including the year of publication. The analysis results show that AI is most commonly applied in the manufacturing, logistics, and finance sectors, focusing on process automation, prediction, and data-driven decision-making. In addition, this study identifies several challenges such as limitations in digital infrastructure, resistance to technology, and the need for regulation and ethical use of AI. This research provides significant contributions in mapping trends and research gaps, as well as offering strategic recommendations for researchers and industry practitioners in developing and implementing AI optimally and sustainably.